2013
DOI: 10.1038/ejcn.2013.196
|View full text |Cite
|
Sign up to set email alerts
|

Dietary factors associated with subclinical inflammation among girls

Abstract: Subclinical inflammation is detectable with increasing BMI and also WHtR. Measures of adiposity (BMI and WHtR) are significant predictors of adiponectin, leptin and hs-CRP. Dietary patterns per se have a small role in affecting inflammatory markers among adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 50 publications
5
42
0
1
Order By: Relevance
“…21 Therefore, the absence of an association in the active group could be mediated partially by the association between sport practice and better eating behaviors in adolescents. 21,23 In the present study, the relationship between inflammation and HDL-c could also explain the findings related to vascular structure in the active group. Physical activity of the group engaged in sports was marginally related to HDL-c, which modulates the phosphorylation of the endothelial nitric oxide synthase and would protect the artery wall through lower blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Therefore, the absence of an association in the active group could be mediated partially by the association between sport practice and better eating behaviors in adolescents. 21,23 In the present study, the relationship between inflammation and HDL-c could also explain the findings related to vascular structure in the active group. Physical activity of the group engaged in sports was marginally related to HDL-c, which modulates the phosphorylation of the endothelial nitric oxide synthase and would protect the artery wall through lower blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Eating behaviors have been suggested as important confounders in the relationship between inflammation and the lipid profile. 20,21 Consumption of some foods seems to control oxidative stress through DNA methylation, 22 and some dietary patterns affect proinflammatory markers in pediatric populations. 21 Therefore, the absence of an association in the active group could be mediated partially by the association between sport practice and better eating behaviors in adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While antioxidant vitamins [19,20] and polyunsaturated fatty acids [19] seem to have anti-inflammatory properties, total fat [20] and saturated fat acids [19,20] seem to be pro-inflammatory. Moreover, a Western dietary pattern is considered to be proinflammatory diet [19].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a Spanish study on obese children from 12 to 17 years of age showed that adiposity measures such as the body mass index (BMI) and waist-to-hip ratio were significant predictors of serum levels of hs-CRP or leptin, and concentrations of adiponectin were positively linked to a Mediterranean dietary pattern [57].…”
Section: Inflammation and Dietary Patternsmentioning
confidence: 99%